Building Resilience Digital Community Ecosystem by Applications Information System and Brand Experience - Kristanto, Harys; Arumdini, Savira; Fardhon, Muhammad; Kurniawan, Wahyu (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2025)
In the face of rapid technological advancements and socio-economic disruptions, digital community ecosystems must develop resilience to ensure sustainability and adaptability. This study investigates how digital applications, information systems, and brand experience contribute to building resilience in Indonesia's land transportation sector. Using a quantitative approach, data were collected from 350 valid responses through online structured questionnaires targeting users of land transportation services, such as buses, trains, and ride-hailing platforms in Jakarta, Bandung, and Surabaya. The sampling was purposive, involving users with prior experience using digital transportation apps. The data were analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The findings indicate that system quality and information quality significantly influence brand experience, which in turn affects user engagement. Furthermore, user engagement plays a crucial role in enhancing the resilience of the digital community ecosystem. The study confirms that brand experience partially mediates the effect of system and information quality on engagement. Implications of the study emphasize the importance for transportation providers to prioritize high-quality, user-centric digital services that foster emotional connection and trust, which are essential to sustaining adaptive and resilient community platforms in the face of urban transportation challenges.